Office work and stretch training (OST) study: effects on the prevalence of musculoskeletal diseases and gender differences: a non-randomised control study. Issue 5 (13th May 2021) - Holzgreve, Fabian; Fraeulin, Laura; Haenel, Jasmin; Schmidt, Helmut; Bader, Andreas; Frei, Markus; Groneberg, David A; Ohlendorf, Daniela; van Mark, Anke
Abstract : Objectives: For the prevention of musculoskeletal diseases (MSDs), stretch training can be a measure of the workplace health promotion (WHP) for office workers. This can lead to an increase in mobility and, ultimately, reduce or prevent MSD. The aim of the study was to examine a standardised and individualised stretch training on a device, specifically 'five Business', for the prevalence of MSD. Design: This study is a non-randomised control study. Setting: WHP programme with clerical employees of a German car manufacturer. Participants: 252 (110 women; 142 men) subjects (median age of 44 (X ∼ 21 years) finished the study successfully. Inclusion criteria included a full-time employment in the office workplace and subjective health. Intervention: The intervention group completed 22–24 training units of 10 min each on the 'five-Business' device two times a week for 12 weeks. Primary and secondary outcome measures: Data were collected in the form of a pre–post study Nordic Questionnaire. Results: After the intervention, significantly fewer subjects reported pain in the area of the neck (−17.79), shoulder (−11.28%), upper back (−14.7%), lower back (−12.78%) and feet (−8.51%). The gender analysis revealed that women are, in general, more often affected by musculoskeletal complaints than men, especially in the neck (+29.5%) and feet (+15.03%). Both sexes had significant reductions of MSD in the most commonly affected regions. Thus, 27.12% less women reported having neck pain, while 13.14% less men reported having low back pain. Conclusions: The results suggest that a stretching programme performed for 3 months can reduce musculoskeletal complaints in the most commonly affected areas in office workers. Both men and women benefited from the stretch training to a similar extent, suggesting that this would be a promising measure for therapy and prevention as part of WHP.